Contribution to determine local runoff in semi arid lands using a remote sensing cartography of surface features - (:unkn) unknown (My University, 1995)
The runoff estimation of small catchments in semi arid lands of Western Africa is poorly known. It is a fact generally accepted that the ground surface is predominant for its explanation. A method to map the surface features by remote sensing was combined with rain simulations in order to map the local runoff. Results were consistent and gave new information on the spatial distribution of runoff in the catchment. Every local runoff obtained by remote sensing techniques was aggregated in order to calculate the whole catchment runoff at the output of the system. This aggregation implies a scaling change problem. Due to the particular hydrological process of these regions, additivity is quite acceptable and permits, in this case, the estimation of global runoff. Out of the Sahelian area, this additivity is less acceptable : scaling problems become more complicated and the method reaches its limits.
Keywords: African Research